Larmor radiation as a witness to the Unruh effect - Higuchi, Atsushi; Matsas, George E. A. [UNESP]; Vanzella, Daniel A. T.; Bingham, Robert; Brito, João P. B.; Crispino, Luís C. B.; Gregori, Gianluca; Vacalis, Georgios (American Physical Society (APS), 2025)
We discuss the emission of radiation from general sources in quantum scalar, electromagnetic, and gravitational fields using the Rindler coordinate frame, which is suitable for uniformly accelerated observers, in the Minkowski vacuum. In particular, we point out that to recover, from the point of view of uniformly accelerated observers in the interaction picture, the usual Larmor radiation, which is independent of the choice of the vacuum state, it is necessary to incorporate the Unruh effect assuming the Minkowski vacuum. Thus, the observation of classical Larmor radiation in the Minkowski vacuum could be seen as vindicating the Unruh effect in the sense that it is not correctly recovered in the uniformly accelerated frame unless the Unruh effect is taken into account.